Teachers' Perspectives on Cultivating Students' Problem-Solving Skills in Higher Vocational Colleges: A Qualitative Analysis Based on The 3P Model - Guan, Xiu; Liu, Yingqun (Journal of educational technology development and exchange, 2025)
Problem-solving skills are critical for students in higher vocational colleges as they prepare for future careers and life challenges. However, cultivating problem-solving skills presents significant challenges. This study investigates the development of students’ problem-solving skills from the perspective of teachers in higher vocational colleges. Fifteen teachers participated in semi-structured interviews, and the data were analyzed using thematic analysis based on the 3P model (Presage - Process - Product). Within this framework, the cultivation of problem-solving skills is conceptualized as a dynamic system comprising three interconnected stages. In the Presage stage, cognitive factors affect the effectiveness of skills development, while non-cognitive factors influence the developmental process. Teachers’ understanding and valuation of problem-solving skills are pivotal for their effective implementation. Moreover, environmental conditions also play a crucial role. In the Process stage, instructional design is guided by instructional objectives, and context-specific teaching methods combined with practical courses have been shown to enhance problem-solving skills more effectively. In the Product stage, teachers rated students’ problem-solving skills as ranging from moderate to below moderate, which they attributed to factors such as low student motivation, limited teacher proficiency, time constraints, and insufficient resources. These insights identify key areas for targeted improvements in the cultivation of problem-solving skills in higher vocational colleges.